Pencegahan dan Penanganan Korban Kekerasan Berbasis Gender dan Anak di Kabupaten Pemalang tahun 2013-2015 - Balqis Dwi Indraswari; Puji Astuti; Fitriyah undip (Journal of Politic and Government Studies, 2018)
The assumption that women and children are weak, makes some of them become victims of violence. The type of violences that occurs are diverse such phisical abuse/ domestic violence, sexual abuse, psychic abuse, human trafficing, economic abuse, etc. The purpose of this study is to describe the implementation of protection trough prevention efforts and treatment by goverment and knowing the use of allocated budget to the victims based on genre and children in Pemalang 2013-2015.The method that used in this study is qualitative approach with data collection technique by interviews and documentations. Informant in this study is Head of Departement Social KBBP Pemalang, Head of improvement quality of life section, Women empowerment and also as Coordinator of Jayandu Widuri Pemalang, Doctor IPKR RSUD Dr. M. Azhari Pemalang, Head of protection of women and children unit (UPPA) Polres Pemalang, and the victims and the family of the victims based on genre and children Pemalang.The study shows that (1) In Pemalang, there are still many women who become victims of phisical abuse / domestic violence which the suspect is their husband, (2) In Pemalang there are many children who become victims of sexual abuse and the suspect is from outside, not the victim’s family (3) The prevention efforts are not yet optimal while the handling efforts are quite optimal (4) The budget allocation still needs to be increased in number. Key Words  :  Women and children violence, preventions, budget